2019
DOI: 10.14202/vetworld.2019.621-628
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic profile of seminal proteins and their correlation with in vitro sperm characters in Black Bengal buck semen

Abstract: Aim: This study aimed to study the electrophoretic properties of seminal plasma and sperm proteins of Black Bengal buck semen and their correlation with in vitro sperm characters and freezability. Materials and Methods: Semen ejaculates from nine Black Bengal bucks were collected by artificial vagina (n=20/buck). Ejaculates were evaluated for in vitro sperm characters and electrophoretic profile of seminal protein. In vitro sperm characters were evaluated immediately after collection, after completion of equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Similar to our findings of individual variation in all parameters except for sperm viability and abnormalities, individual variation in semen volume, sperm motility and viability, mass movements, sperm concentration, membranes integrity, acrosome integrity [9], and sperm abnormalities [39] has been found in goats as well as in boar sperm motility, MI, and mitochondrial activity [40].…”
Section: Individual Variation In the Quality Of Fresh Semensupporting
confidence: 90%
“…Similar to our findings of individual variation in all parameters except for sperm viability and abnormalities, individual variation in semen volume, sperm motility and viability, mass movements, sperm concentration, membranes integrity, acrosome integrity [9], and sperm abnormalities [39] has been found in goats as well as in boar sperm motility, MI, and mitochondrial activity [40].…”
Section: Individual Variation In the Quality Of Fresh Semensupporting
confidence: 90%
“…The sperm motility percentage was categorized normal based on the SNI 4869-1:2017 requirement for post-thawing frozen semen with minimum mobility of 40% [20]. Karunakaran et al [8] showed that generally after the process of freezing and thawing, sperm motility decreases by around 34%-46%. Cryopreservation and the freeze-thawing phase causes detrimental effects, such as stress induced by chemical, physical, and osmotic pressure, or changes in the temperature of the sperm [21].…”
Section: Discussion the Post-freeze Thawing Quality Of Holstein Bull Sperm And The Correlation With Fertility Levelmentioning
confidence: 99%
“…A specific protein in the semen can change its function and affect the fertility of sperm [7]. It is reported that several proteins in the sperm and seminal plasma could be used as indicators of sperm characters, quality, and fertility levels [7,8]. Detected proteins in the sperm are related to the bull's fertility, such as a heparin-binding protein with a molecular weight (MW) of 31 kDa [9] and phospholipase A2 with an MW of 16 kDa [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies conducted in bull, ram and buck revealed that quantitative variations in seminal plasma and sperm proteins also appeared between males [90][91][92][93][94][95][96], which could explain in part the individual variability observed in sperm freezability [97,98]. Males are frequently categorized as good or bad freezers depending on their post-thaw sperm quality; however, molecular biomarkers could predict more efficiently sperm cryotolerance before freezing-thawing in different individuals [10].…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%